THE SPECIAL FEATURES OF THE STATE FINANCIAL POLICY - Vlasiuk, V. Ye. (Science and Transport Progress, 2008)
The article is devoted to the theoretical-and-methodical problems of research of conduction of the state financial policy peculiarities. The approaches to formation of the state profits are analyzed.